Analisis Faktor yang Berhubungan Dengan Kualitas Bekteriologis Air Minum Isi Ulang Tingkat Produsen Di Kota Semarang Tahun 2004. - Asfawi, Supriyono; Nurjazuli, Nurjazuli; Sulistiyani, Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2004)
ABSTRACK Background:Water represents an absolute medium to human life and other living things. However, water can also be the best media of diseases to spread. Therefore, before consumed, water has to be processed drinking to eliminate or degrade impure materials up to the safest level. As water becomes more problematic these days, it attracts the attention of drinking water refill depots to. Furthermore, dringking water that produce is not yet legalized and standardized in terms of its process. This research to know determine factors related to bacteriological quality of drinking water product drinking water refill in Semarang City. Methods:This research was an Explanatory Research. Using observation with a cross sectional approach. Samples are determined with standard error of 10% from 49 depots divided proportionally towards the spreading of depots throughout Semarang city. The variables used are a parameter of the bacteriologic number of coliform, E_Coli germs. Data analysis using Test correlation of kontingensi chi-square to know relation between variable. Results:The result of this research shows the relation to the variables using Chi-square test, it is shown that the condition of standard water and the condition of Bacteria of refill drinking water are C = 0,494, p = 0,0001, consequently Ho rejects it. Correlation test of instrument condition and the bacteriologic quality of refill drinking water showed that when C = 0,178, p = 0,447, Ho accepts it. While correlation test of processing of drinking water and the bacteriologic quality of refill drinking water showed that when C = 0,346, p = 0,035, Ho rejects it. Correlation test of hygienic officer of depot and the bacteriologic quality of refill drinking water shows that when C = 0,263, p = 0,162, so Ho accepts it. And correlation test of DAMIU sanitation and the bacteriologic quality of refill drinking water showed that C = 0,512, p = 0,0001, so Ho rejects it. Conclusions: All depots have not yet met the requirements of producing standard water as requested by Department of Health. The hygienic behavior of workers is still poor. The bacteriologic quality of refill drinking water based on the result of lab. test indicates that 34 samples ( 69,4%) have fulfilled the requirements of standard drinking water but the rest have not yet reached the minimum standard of drinking water. This matter is caused by the standard water which is used, the procedure of processing and the environmental condition of depot. Keyword; drinking water, refill depots, bacteriology quality